Testimony, time and structure in Tropics An homage to Claude Lévi-Strauss (1908-2009) - Arana Bustamante, Luis (2010)
A new lecture of a fundamental book of the author, Tristes Tropiques (1955) will be our guideline to look on some premises of his method and thought. The aim is to remark its trascendence to human sciences and general social theory, and to make clear the author’s constant consciousness about the particular historic moment of a singular social or etnographic observation. Also to mention briefly some of his thoughts and points of view about cultural and historical transformation —later developed by himself— that pointed beyond of the circunscription of structuralist procedures to strict synchronistic social situations. Thus structuralism is now open to the study of structural transformation, an aspect studied by later scholars on the basis of part of Levi Strauss’s approaches.